Genetic characterization of Trypanosoma cruzi DTUs in wild Triatoma infestans from Bolivia: predominance of TcI. - Simone Frédérique Brenière; Claudia Aliaga; Etienne Waleckx; Rosio Buitrago; Renata Salas; Christian Barnabé; Michel Tibayrenc; François Noireau (Public Library of Science (PLoS), 2012)
BACKGROUND: The current persistence of Triatoma infestans (one of the main vectors of Chagas disease) in some domestic areas could be related to re-colonization by wild populations which are increasingly reported. However, the infection rate and the genetic characterization of the Trypanosoma cruzi strains infecting these populations are very limited. METHODOLOGY/PRINCIPAL FINDINGS: Of 333 wild Triatoma infestans specimens collected from north to south of a Chagas disease endemic area in Bolivia, we characterized 234 stocks of Trypanosoma cruzi using mini-exon multiplex PCR (MMPCR) and sequencing the glucose phosphate isomerase (Gpi) gene. Of the six genetic lineages ("discrete typing units"; DTU) (TcI-VI) presently recognized in T. cruzi, TcI (99.1%) was overdominant on TcIII (0.9%) in wild Andean T. infestans, which presented a 71.7% infection rate as evaluated by microscopy. In the lowlands (Bolivian Chaco), 17 "dark morph" T. infestans were analyzed. None of them were positive for parasites after microscopic examination, although one TcI stock and one TcII stock were identified using MMPCR and sequencing. CONCLUSIONS/SIGNIFICANCE: By exploring large-scale DTUs that infect the wild populations of T. infestans, this study opens the discussion on the origin of TcI and TcV DTUs that are predominant in domestic Bolivian cycles.